Prophets and Princes on Isles of Ocean: A ‘Call’ for an Old Testament Style Regime in Vita Columbae - Enright, Michael J. (Peritia, 2010)
Abstract Though Adomnán refers to Columba as saint and holy man, he seeks most earnestly to portray him as a prophet who closely follows an Old Testament pattern of prophetic initiation and behaviour. In the light of scriptural characteristics of prophecy and of the ‘called’ and ‘sent’ prophets, Vita Columbae iii 1-5 is analysed to show how each chapter is crafted to correspond to the inheritance of prophetic power that culminates in a ‘call’ to the prophet. Eleven other chapters on battles, princes, and rulers are studied to show the consistent elaboration of the prophetic pattern as applied to the islands of the Insular world. All major kingship questions in the vita are illuminated: the presence of the battle-champion motif and other matters centring on the kings, Oswald, Diarmait mac Cerbaill, Áed Slaine, and Áedán mac Gabrain. A lucid picture of Adomnán’s mode of thinking about the reformation of kingship and the relationship of political authority to God’s plan emerges.